Pengaruh Perilaku Personal Hygiene Terhadap Infeksi Luka Gangren Pada Pasien DM Tipe II di RSU Royal Prima Medan Tahun 2025 - Serani Waruwu; Elvina Nathania Zega; Sella Febina Sembiring; Ruth Vitha Sari Purba; Anggun Nirawan Limbong; Tiarnida Nababan (Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes mellitus is a chronic disease that occurs when the pancreas does not produce enough insulin. Increased glucose levels in the body are a sign of symptoms of insulin resistance, dry mouth, fatigue, weakness, and susceptibility to infection or wounds. DM with abnormal glucose levels can cause damage to peripheral blood vessels and susceptibility to infection that can lead to gangrene wounds, which is the loss of sensation in the lower extremities and can risk amputation. Gangrene can be prevented by improving personal hygiene. Good personal hygiene is very influential on gangrene wounds of patients with DM, this is to prevent damage to skin integrity. Purpose: To determine and analyze the effect of personal hygiene behavior on gangrene wound infection in type II DM patients. Methods: This type of research is quantitative with a cross-sectional design. The population in this study were all 325 people with type II DM. The research sample used simple random sampling method, namely 50 people. data collection was obtained from the results of questionnaires distributed to respondents. Data analysis using the chi-square test. Results: the final result using the chi- square test obtained a p value of 0.000 <0.05. Conclusion: There is a significant correlation between personal hygiene behavior and the incidence of gangrene wound infection in type II DM patients. This study is expected to be a source of reference in developing research related to personal hygiene behavior, gangrene wound infection, and type II DM. Keywords:Behavior, personal hygiene, DM, wound infection, gangrene